Evaluating the responsiveness of the Warwick Edinburgh Mental Well-Being Scale (WEMWBS): Group and individual level analysis - Maheswaran Hendramoorthy; Weich Scott; Powell John; Stewart-Brown Sarah (Health and Quality of Life Outcomes, 2012)
Abstract Background Mental well-being now features prominently in UK and international health policy. However, progress has been hampered by lack of valid measures that are responsive to change. The objective of this study was to evaluate the responsiveness of the Warwick Edinburgh Mental Well-being Scale (WEMWBS) at both the individual and group level. Methods Secondary analysis of twelve different interventional studies undertaken in different populations using WEMWBS as an outcome measure. Standardised response mean (SRM), probability of change statistic (P̂) and standard error of measurement (SEM) were used to evaluate whether WEMWBS detected statistically important changes at the group and individual level, respectively. Results Mean change in WEMWBS score ranged from −0.6 to 10.6. SRM ranged from −0.10 (95% CI: -0.35, 0.15) to 1.35 (95% CI: 1.06, 1.64). In 9/12 studies the lower limit of the 95% CI for P̂ was greater than 0.5, denoting responsiveness. SEM ranged from 2.4 to 3.1 units, and at the threshold 2.77 SEM, WEMWBS detected important improvement in at least 12.8% to 45.7% of participants (lower limit of 95% CI>5.0%). Conclusions WEMWBS is responsive to changes occurring in a wide range of mental health interventions undertaken in different populations. It offers a secure base for research and development in this rapidly evolving field. Further research using external criteria of change is warranted.